2007
DOI: 10.1021/jf070799z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tomato Phenolics to Antioxidation and Down-regulation of Blood Lipids

Abstract: This study was performed to understand the characteristics and biological activities of phenolics in tomatoes and to examine the effect of tomato on the regulation of blood lipids. Tomatoes of both big and small sizes were used fresh, after blanching, or after blanching and heating. Moreover, a human clinical trial was conducted to examine plasma antioxidation, status of blood lipids, and phenolic responses after ingestion of fresh tomato, tomato juice, and a lycopene drink. The contents of tomato phenolics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 33 publications
(32 reference statements)
2
63
1
3
Order By: Relevance
“…A measure of protection against oxidative stress was significantly increased in all three treatment groups. 87 Shen et al 88 (2007) treated 24 subjects with either fresh tomato, tomato juice, or a lycopene drink (all delivering 40 mg lycopene/day) for six weeks. It was found that triglyceride levels and LDL were decreased, and high-density lipoprotein (HDL) increased in subjects who consumed fresh tomato and tomato juice.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A measure of protection against oxidative stress was significantly increased in all three treatment groups. 87 Shen et al 88 (2007) treated 24 subjects with either fresh tomato, tomato juice, or a lycopene drink (all delivering 40 mg lycopene/day) for six weeks. It was found that triglyceride levels and LDL were decreased, and high-density lipoprotein (HDL) increased in subjects who consumed fresh tomato and tomato juice.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…It was found that triglyceride levels and LDL were decreased, and high-density lipoprotein (HDL) increased in subjects who consumed fresh tomato and tomato juice. 88 Bohn et al 89 (2009) demonstrated that soy tomato beverage consumption significantly reduced LDL+VLDL levels and increased HDL levels in 18 healthy men and women.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Post harvest heat treatment of tomatoes affects fruit ripening and decay (Falik, 1993). Shen et al (2007) reported increases in the phenolic content of big and small tomatoes by blanching and heating. Tomato phenolics showed fair antioxidant activity and synergistically promoted the antioxidation of tomato carotenoids and may play an important role in the chemoprevention of cancer (Shen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genetics, environment, cultural practices and post harvest handling and processing (Shen et al, 2007) can impact the phyto-chemical composition of tomatoes. Preharvest approaches at improving tomato nutritional quality and health benefits attempt to harness natural Science Publications AJAVS genetic variation (Melendez-Martinez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation